2021
DOI: 10.3390/app11072935
|View full text |Cite
|
Sign up to set email alerts
|

Global Study of Human Heart Rhythm Synchronization with the Earth’s Time Varying Magnetic Field

Abstract: Changes in geomagnetic conditions have been shown to affect the rhythms produced by the brain and heart and that human autonomic nervous system activity reflected in heart rate variability (HRV) over longer time periods can synchronize to changes in the amplitude of resonant frequencies produced by geomagnetic field-line and Schumann resonances. During a 15-day period, 104 participants located in California, Lithuania, Saudi Arabia, New Zealand, and England underwent continuous ambulatory HRV monitoring. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…With a more differentiated analysis of the noise changes on different time scales [ 328 ], individual phases of stability could be identified via the rates of change, which support interventions. The extent to which the apparently unmotivated changes are due to genetic aging processes [ 343 , 344 ] or to variations in the Earth’s magnetic field [ 345 , 346 , 347 ] opens up extensive further areas of research, again supporting Duhem and Quine’s holism argument and the problem of absolute knowledge. If temporal change is a characteristic of the object of study, then it should be studied in more detail in the movement and, especially, learning sciences, in analogy to the properties of a rigid body in physics.…”
Section: Perspectivementioning
confidence: 99%
“…With a more differentiated analysis of the noise changes on different time scales [ 328 ], individual phases of stability could be identified via the rates of change, which support interventions. The extent to which the apparently unmotivated changes are due to genetic aging processes [ 343 , 344 ] or to variations in the Earth’s magnetic field [ 345 , 346 , 347 ] opens up extensive further areas of research, again supporting Duhem and Quine’s holism argument and the problem of absolute knowledge. If temporal change is a characteristic of the object of study, then it should be studied in more detail in the movement and, especially, learning sciences, in analogy to the properties of a rigid body in physics.…”
Section: Perspectivementioning
confidence: 99%
“…We have also investigated HRV in the context of social and global coherence and heart rhythm synchronization between pairs of people (McCraty, 2004 , 2015a ) and in groups (McCraty, 2017 ), as well as how HRV can synchronize with the power of the resonant frequencies in Earth’s magnetic field (McCraty & Deyhle, 2015 ; McCraty et al, 2017 ; Timofejeva et al, 2021 ). In a recent study of groups located in five countries it was found that being in a more coherent HRV rhythm for fifteen minutes increased synchronization not only among group members in each of the groups, it also increased the HRV synchronization with the Earth’s magnetic field over the following 24-h period (Timofejeva et al, 2021 ).…”
Section: Hrv Research Contributionsmentioning
confidence: 99%
“…In a recently published study, 104 participants from five countries completed 15 days of ambulatory HRV monitoring. Analysis of participants HRV before, during, and after a Heart Lock-In meditation period indicated significantly increased coherence, as well as correlation with magnetic field activity on the day of the meditation [ 45 ].…”
Section: Heartmath Global Healthcare Meditationmentioning
confidence: 99%